Understanding climate change anxiety and anticipatory climate disaster stress: A survey of residents in a high-risk California county during wildfire season - E Alison Holman; Tiffany Junchen Tao; Kayley D Estes; Farshid Vahedifard; Roxane Cohen Silver (BMJ Mental Health)
Background With the increasing prevalence of climate-related disasters, psychological responses, including climate change anxiety and anticipatory climate disaster stress, have received heightened attention.Objective We investigate the correlates of climate change anxiety and anticipatory climate disaster stress, as well as the nature of these psychological responses.Methods At the start of the annual fire season (June to August 2023), we recruited a county-representative sample of n=813 residents of Lake County, in Northern California, to complete an anonymous online survey. Multiple regression analyses identified correlates of climate change anxiety and anticipatory climate disaster stress and explored how anxiety and stress were associated with disaster preparedness.Findings Climate change anxiety, assessed via its cognitive-emotional impairment (odds ratio (OR)loss/injury=1.68; ORmedia=2.37) and functional impairment (ORloss/injury=1.68; ORmedia=2.63) subfactors, and anticipatory climate disaster stress (bloss/injury=0.15, bmedia=0.26) were associated with previous wildfire-induced loss/injury and media exposure to wildfire-related content. Anticipatory climate disaster stress was also associated with the frequency of being in an evacuation zone (b=0.05). Both the cognitive-emotional impairment subfactor of climate change anxiety (incidence rate ratio (IRR)=1.23) and anticipatory climate disaster stress (IRR=1.14) were associated with preparing an emergency kit and power outage supplies; anticipatory climate disaster stress was associated with evacuation intentions should an actual fire occur (b=0.12).Conclusions Prior experiences with climate disasters could explain people’s psychological responses to climate change. These responses could be temporally appropriate and functionally adaptive, given the immediacy of a potential fire.Clinical implications Climate change anxiety and anticipatory climate disaster stress should not be oversimplified as typical clinical symptoms because their presence might motivate adaptive self-protective behaviours in the face of an upcoming disaster.